Public innovation, an advance towards a more efficient state: the case of the Secretarìa de Educacion of the District of Bogotá (2020)
This essay offers an opinion to reflect on innovation in the public sector, how it reaches Colombia and the mechanisms through which its implementation begins until analyzing the state of execution for the specific case of the Secretaría de Educación Distrital. Different approaches are identified on public innovation and the evolution of the dialect that has generated introduction in the public sector that generates the cultural change of the public servant and the involvement of the citizen to achieve more effective and efficient services that provide solutions to public problems.